2017
DOI: 10.1155/2017/1526209
|View full text |Cite
|
Sign up to set email alerts
|

Indoor/Outdoor Air Quality Assessment at School near the Steel Plant in Taranto (Italy)

Abstract: This study aims to investigate the air quality in primary school placed in district of Taranto (south of Italy), an area of high environmental risk because of closeness between large industrial complex and urban settlement. The chemical characterization of PM2.5 was performed to identify origin of pollutants detected inside school and the comparison between indoor and outdoor levels of PAHs and metals allowed evaluating intrusion of outdoor pollutants or the existence of specific indoor sources. The results sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 45 publications
1
12
1
Order By: Relevance
“…The relationship between personal, indoor and outdoor measurements was assessed. Our data are consistent with the general pattern observed in most PM monitoring studies [ 34 , 35 , 36 , 37 ]: outdoor levels are lower than indoor levels, and both indoor and outdoor levels are lower than personal levels. Elemental components in outdoor PM 2.5 filter mass are higher than indoors.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The relationship between personal, indoor and outdoor measurements was assessed. Our data are consistent with the general pattern observed in most PM monitoring studies [ 34 , 35 , 36 , 37 ]: outdoor levels are lower than indoor levels, and both indoor and outdoor levels are lower than personal levels. Elemental components in outdoor PM 2.5 filter mass are higher than indoors.…”
Section: Discussionsupporting
confidence: 92%
“…Exposure of artisanal cookware makers during cookware making is undocumented in the literature. Some studies conducted previously have shown that microenvironment assessment does not always reflect personal exposure [ 34 , 35 , 36 ]. Similarly, concurrent samples undertaken in this study revealed that the averaged personal exposure levels (3-h mean) at breathing zones of workers are much greater (490 µg/m 3 ) than those of the microenvironment levels.…”
Section: Discussionmentioning
confidence: 99%
“…The PAH concentration in the research area was higher than in a study by Di Gilio et al, as the indoor concentration was up to 2.36 ng m −3 at a school near the steel industrial area [ 58 ]. BbF, BgP, IcP, BkF, and DbA species were identified as the most abundant constituents in that study, which was scientifically known as a proxy for traffic and coke oven emissions.…”
Section: Resultsmentioning
confidence: 82%
“…Such topics are important because, based on the subpopulation interested, such as suggested by Manigrasso et al [50], which estimated the particle regional respiratory doses for both combustion and non-combustion aerosol sources currently encountered in microenvironments, with special regards to the age of subjects. Recent papers on school environments are related to monitoring PM, NO x , VOCs, and CO 2, with regard to the ventilation efficiency and the energy consumption [51][52][53][54][55][56]. As to the radon exposure, according to two papers, the schools are vulnerable targets due to the long daily childhood presence, and the radon risk could be reduced by low-cost interventions (e.g., implementation of natural air ventilation and school maintenance) [57,58].…”
Section: Rapp Istisanmentioning
confidence: 99%